Assessment of Nutritional Status in Children With Cancer and Effectiveness of Oral Nutritional Supplements. (18th August 2015) - Gürlek Gökçebay, Dilek; Emir, Suna; Bayhan, Turan; Demir, Hacı Ahmet; Gunduz, Mehmet; Tunc, Bahattin
Abstract : Malnutrition is a common consequence of cancer in children, but the most effective methods of nutrition intervention are under debate. We aimed to evaluate the nutritional status of children diagnosed with cancer, and to investigate the effect of oral nutritional supplements on anthropometric measurements, biochemical parameters, and outcome. A randomized clinical study of 45 newly diagnosed cancer patients was performed. Anthropometric and biochemical data and related factors were assessed at 0, 3, and 6 months after diagnosis. On initial anthropometric assessment, prevalence of malnutrition by weight or height was found to be lower as compared with body mass index (BMI), or weight for height (WFH), or arm anthropometry. Twenty-six of the patients (55%) received oral nutritional supplement. During the second 3 months after diagnosis, there was a statistically significant decrease in number of the patients with WFH <90th percentile and BMI <5th percentile ( P = .003 and P = .04, respectively). Infectious complications occurred more frequently in malnourished patients during first 3 months, and survival of children who were malnourished at the 6th month was significantly lower than that of well-nourished children ( P = .003). On laboratory assessment, serum prealbumin levels of the all subjects were below normal ranges, but no relation was found for serum prealbumin or albumin levels in patients who were malnourished or not at diagnosis. Nutritional intervention is necessary to promote normal development and increase functional status as a child receives intensive treatment. Protein- and energy-dense oral nutritional supplements are effective for preventing weight loss in malnourished children.